ANALISIS KANDUNGAN KIMIA EKSTRAK BIJI MAHONI DENGAN PELARUT KLOROFORM DAN METANOL - Moreira, Ilídio Ximenes; M. Kopong, Aloysius; H. B. Hayon, Vinsensia (STKIP PGRI Situbondo, 2024)
Mahogany is a plant that grows freely in forests, gardens, and various areas and as a plant that has the benefits and economic value. However, now mahogany has been cultivated and is known as a traditional medicinal plant for humans and animals. The objective of this research is to identify the chemical compounds contained in the mahogany seed extract with methanol and chloroform solvents. The research used mahogany seeds with methanol and chloroform solvent. After that, was analyzed by Thin Layer Chromatography (TLC) and GC-MS instrument. The results of the TLC test when used the methanol solvent with eluent chloroform: ethyl acetate: n-hexane as 4 points, an Rf value are 0.2237; 0.3818; 0.4727; and 0.6363. The eluent of chloroform solvent is n-Hexane: ethyl acetate as 5 points, Rf value are 0.1145; 0.2581; 0.3709; 0.5855; and 0.6709. Then, it was analyzed with the GC-MS instrument, revealing that the mahogany seed extract from each solvent contained 26 peaks for the methanol solvent and 16 peaks for the chloroform solvent. Therefore, it was analyzed with the GC-MS instrument, revealing that the mahogany seeds extract as 26 peaks for the methanol solvent and 16 peaks for the chloroform solvent. Thus, can be concluded that the mahogany seeds extracts with methanol and chloroform solvents have the same and also different contents and compound groups, depending on the polarity of the groups and/or compounds contained in mahogany seeds towards methanol and chloroform solvents. Therefore, concluding that the seeds extract with methanol and chloroform solvents contain the same compounds and different compounds depends on the polarity of the groups/or substance in the mahogany seeds with methanol and chloroform solvent. That’s way, we would like suggest to the future researchers be able to isolate the chemical content of the mahogany seeds and test their toxicity.